PENGARUH PENDEKATAN HEUTAGOGY TERHADAP HASIL BELAJAR KETERAMPILAN KERJA PESERTA PELATIHAN DI LPK JAPAN LINK INDONESIA - Megawati; Safuri Musa; Ika Rizqi Meilya (Learning Society: Jurnal CSR, Pendidikan dan Pemberdayaan Masyarakat, 2026)
The improvement of job training quality has become an important necessity in responding to the continuously evolving labor market demands. Training institutions are required not only to provide training materials but also to implement learning approaches that effectively develop trainees’ work skills. One learning approach relevant to adult learners is heutagogy, which emphasizes learner autonomy, self-reflection, adaptability, and learning capability. This study aimed to determine the effect of the heutagogy approach on trainees’ work-skill learning outcomes at LPK Japan Link Indonesia, Karawang Regency. The study employed a quantitative approach using an explanatory survey method. The population consisted of 50 trainees, all of whom were selected as research participants through total sampling. Data were collected through questionnaires and analyzed using simple linear regression. The results showed that the data were normally distributed (Sig. = 0.087), the relationship between variables was linear (Deviation from Linearity Sig. = 0.174), and no heteroscedasticity was found. The regression equation obtained was Y = 7.505 + 0.645X. Hypothesis testing indicated that the t-value (12.304) was greater than the t-table value (2.011) with a significance level of 0.000 < 0.05. The coefficient of determination (R²) was 0.759, indicating that the heutagogy approach contributed 75.9% to trainees’ work-skill learning outcomes. The findings indicate that the heutagogy approach has a positive and significant effect on trainees’ work-skill learning outcomes.